The Effect of Financial Literacy and Use of Financial Technology (FinTech) on Financial Behavior: (Study of Micro, Small and Medium Enterprises, MSMEs in Bandung Regency) - Hidayat, Rifki; Aceng Kurniawan (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Analyzing the Influence of Financial Literacy and the Use of Financial Technology (FinTech) on Financial Behavior in Bandung Regency Micro, Small and Medium Enterprises (MSMEs). Design/methodology/approach: This research uses a quantitative approach through correlational methods. Research Findings: The research results found: 1). Financial literacy has a positive and significant effect on financial behavior variables. 2). The use of financial technology (FinTech) has a positive and significant effect on financial behavior variables. 3). Financial literacy and the use of financial technology (FinTech) positively and significantly affect the financial behavior of micro, small and medium enterprises (MSMEs) in Bandung Regency. Theoretical Contribution/Originality: Further increase knowledge of financial management by actively participating in workshops or seminars related to financial management, insurance, investment and business fund management. And increasing financial technology (FinTech) knowledge by orienting to the latest news regarding technological developments in up-to-date financial products and services.